Contagious holiness Jesus' meals with sinners - Blomberg, Craig L. (Leicester, UK IVP, 2005)
Includes bibliographical references and indexes.
Keywords: Holiness (theology).; Jesus Christ -- friends and associates; Bible. N.T. -- criticism, interpretation, etc; Dinners and dining in the Bible